A Model of the Bimetallic System - Oppers, S. (Washington, D.C. : International Monetary Fund, 1995)
This paper formalizes Irving Fisher's century-old model of bimetallism and adds the important 'disequilibrium' dynamics to deal with the long periods during which bimetallic countries were on effective monometallic standards. It resolves a long standing puzzle in the bimetallic literature regarding the remarkable stability of the gold/silver price ratio in the nineteenth century by modeling the bimetallic mint ratio as a regulating barrier to the gold/silver price ratio. It thus provides a clean-cut example of a target-zone model that-in contrast to other such models in the literature-exhibits the main predicted nonlinearities in the data. This is a Paper on Policy Analysis and Assessment and the author(s) would welcome any comments on the present text. Citations should refer to a Paper on Policy Analysis and Assessment of the International Monetary Fund, mentioning the author(s) and the date of issuance. The views expressed are those of the author(s) and do not necessarily represent those of the Fund.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet